MUCOCELE OF THE APPENDIX: THROUGH 8 CASES AT MILITARY HOSPITAL 175 - Nguyen Van , Manh; Doan Thanh , Huy; Nguyen Manh , Khoe; Truong Duc , Cuong (Tạp chí Y Dược Thực hành 175, 2024)
Appendiceal Mucocele (AM) is a very rare disease, believed to be more common in middle-aged women, and includes both non-neoplastic and neoplastic lesions. If not diagnosed and treated early, it can lead to mucin leakage, spilling into the peritoneal cavity, resulting in severe consequences, particularly the complication of pseudomyxoma peritonei (PMP), which has a very poor prognosis. Although it is not difficult to preoperatively diagnose AM using imaging diagnostic tools such as computed tomography and ultrasound, but screening and early detection of appendiceal mucocele still face many difficulties because the clinical symptoms of AM are quite faint. Accurate and thorough surgical resection is the main treatment method, and the subsequent histopathological analysis forms the basis for the next treatment steps. We report 8 cases of AM diagnosed and treated at the Abdominal Surgery Department of Military Hospital 175 with positive treatment outcomes.